Webinar Pelatihan Manajemen UKK KSR PMI Unit IAIN Pekalongan - Riska Alinda; Nabila Syakira; Muhlisin; Syarif Hidayatullah (Jurnal Pengabdian Kepada Masyarakat (JPKM) Langit Biru, 2022)
UKK KSR PMI Unit IAIN Pekalongan has implemented one of the work programs of the Infokom (Information and Communication) Division, namely Webinar Management Training with participants representing members of each division of UKK KSR PMI Unit IAIN Pekalongan. Webinar Management Training is conducted to provide training to administrators so that they can and know what webinar management is and how to do it. In this event, there were two learning discussions presented by Adhi Bagus Wijarnako and Muhammad Fauzan. The first theory was explained by Adhi Bagus Wijarnako who explained how to make certificates and additional applications used to reproduce the certificate such as the PDF Split Merge application. Before the activity started, participants were given application links and what files were needed in making the certificate. Furthermore the second theory was presented by Muhammad Fauzan regarding the management of the Zoom Meeting application. The provision of facilities in the form of an access link for the operation of making certificates has been prepared before the event begins. Then it was continued with a discussion on making certificates and procedures for managing the Zoom Meeting application. The purpose of holding this event is so that the management and members of UKK KSR PMI Unit IAIN Pekalongan can know and operate the Zoom Meeting application management and procedures for making certificates. The method used is a direct method and a description of each presentation. With this Webinar Management Training activity, it is hoped that the management and members of UKK KSR PMI Unit IAIN Pekalongan can find out new understandings as technology develops and can be applied in various other activities.